O ensino de Lacan - Viana Vidal, Paulo Eduardo (Poiésis, 2014)
The purpose of this article is to demonstrate that we need to talk about J. Lacan’s teaching and not J. Lacan’s work, theory or system, because his legacy it is not a deduction of an already known knowledge, but an elaboration of knowledge in action, which present at least three phases.